Las actividades lúdicas: herramienta pedagógica interesante para mejorar la ortografía en el sexto grado de Educación General Básica - Maza Cabrera, Gladis Guisela (2023)
The Curricular Integration Work entitled "Playful Activities: An Interesting Pedagogical Tool for Improving Spelling in Sixth Grade Students of General Basic Education" has the following general objective: To determine the influence of playful activities on the improvement of spelling in the sixth grade students of General Basic Education. This is a descriptive research with a mixed approach and quasi-experimental design. The theoretical framework addressed the variables of playful activities and spelling. During the research process, the methods employed included scientific, descriptive, analytical, synthetic, and statistical approaches. To gather information, an interview was conducted with the teacher, and a diagnostic spelling test was administered to the students. The research population was thirty-one students and a teacher from "José Ingenieros" Basic Education School. Initial results indicate that a high percentage of the investigated students do not have mastery over the subject matter, and a significant percentage is close to achieving mastery. In order to contribute to the improvement of spelling, an alternative proposal called "Learning Spelling through Games" was designed and implemented. This proposal proved effective in enhancing the spelling skills of the students, as confirmed by the second administration of the spelling proficiency test. The data from the test demonstrated that a substantial number of students have mastered the subject matter, while another percentage has achieved mastery. In conclusion, playful activities serve as an interesting and effective pedagogical tool for enhancing spelling skills. Therefore, educators are encouraged to incorporate selected playful activities to improve spelling and contribute to the attainment of educational quality.